Program Development Strategies in Achieving the Vision and Mission of the Faculty Through the Understanding of Academic Community (Sumatra Journal of Disaster, Geography and Geography Education, 2023)
The vision of the Faculty of Education and Teacher Training at Pattimura University is to create an outstanding faculty that produces professional, innovative, and ethical educators. The mission of the faculty is to produce graduates who have academic ability, strong character, and reliable professional skills. The purpose of this research is to measure the level of academic community understanding about the implementation of the vision and mission, and to provide strategies to achieve them. The study was conducted at the Faculty of Education and Teacher Training at Pattimura University, using a quantitative descriptive method with a total of 158 respondents. The results of the research showed that the sources of information were from the website and online media, and the academic community had a good understanding of the faculty's vision and mission. The academic community also evaluated the support from the faculty in achieving its vision and mission. To improve understanding and achieve the faculty's vision and mission, strategies such as optimizing the faculty website's user-friendly display, improving available facilities, regularly optimizing the use of social media to reach out to the public, enhancing the quality of educators, and developing a network of cooperation among educational institutions should be implemented